1993
DOI: 10.1002/ps.2780380106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wind direction, wind speed and travel speed on spray deposition

Abstract: Deposition variability from a conventional field sprayer, and effects of wind and travel speed were measured by collecting on small artificial targets in the swath. Whilst deposition on 0.1-m2 plots varied by a factor of 3, deposition on single vertical targets typically varied by a factor of 10 and on horizontal targets by a factor of 6. Distinct transversal deposition patterns appeared according to wind direction. The quantity and structure of variability was compared with wind speed and turbulence intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…the coarseness of droplets, and higher retention efficiency was consistently demonstrated with finer-droplet sprays. Increasing travel speed may improve spray collection on more vertical surfaces (Nordbo et al 1993), but this effect was not found significant in this study. The speeds used in this study may be too slow, and a track sprayer with a wider range of speed choices (Wolf et al 2000) may help determine this effect more accurately.…”
Section: Resultscontrasting
confidence: 60%
“…the coarseness of droplets, and higher retention efficiency was consistently demonstrated with finer-droplet sprays. Increasing travel speed may improve spray collection on more vertical surfaces (Nordbo et al 1993), but this effect was not found significant in this study. The speeds used in this study may be too slow, and a track sprayer with a wider range of speed choices (Wolf et al 2000) may help determine this effect more accurately.…”
Section: Resultscontrasting
confidence: 60%
“…It is not entirely clear why the youngest leaf was consistently less diseased. This emerging leaf is more vertically positioned, conceivably retaining less spray (Nordbo et al 1993). However, a separate study found that the retention was not significantly different among leaves of different positions, suggesting an equivalent amount of pathogen inoculum on all leaves (Peng et al 2001).…”
Section: Effect Of Weed Growth Stage On Biocontrol Efficacymentioning
confidence: 99%
“…As a result, many sprayers are now configured with their nozzles angled 30 to 45Њ forward to facilitate spray deposition. Faster travel speeds also impart more horizontal trajectories to the spray (Nordbo et al 1993). In notill, vertically oriented stubble canopies may, like grassy weeds, be preferentially targeted by forward-oriented spray trajectories, reducing spray penetration.…”
mentioning
confidence: 99%